Impact of Variable Speed Drive Jobsheet Integrated with Project-Based Learning Model on Electric Motor Control Skills of Vocational Students - Setyawan, Herlin; Sukardi, Sukardi; Risfendra, Risfendra; Putri, Meri Yulianti; Oktavia, Vivi; Ambiyar, Ambiyar; Wulansari, Rizky Ema (Universitas Negeri Padang, 2023)
The problem in this study is that many students in the electrical power installation engineering (EPIE) class have not mastered the skills of electric motor control (EMC). This is because the teacher still uses traditional methods in the learning process. Namely, the teacher actively explains the material according to practical experience rather than referring to EMC learning objectives. This study aims to apply a variable speed drive (VSD) jobsheet based on project-based learning (PjBL) in the EMC learning process and measure the effectiveness of the jobsheet applied. The research method used was a pre-experiment with an intact group comparison research design. The research subjects were taken from 11th-grade students of vocational schools majoring in electrical power installation engineering and were assessed using a questionnaire instrument to evaluate students' EMC performance. Data analysis techniques used were independent t-test and effect size test. Based on the independent t-test analysis results, the t-value is larger than the t-table (t = 4.936 > 1.99962), and the significance value is 0.000, which shows a significant difference in skills between the experimental and control classes. Based on the effect size analysis, the value is 1.243, which means the jobsheet can improve students' EMC skills in the large category. Based on these two results, it is known that the PjBL-based VSD jobsheet is effective in the EMC learning process. Thus, it is expected that EPIE vocational high schools can use the PjBL-based VSD Jobsheet in the EMC learning process.